Intra-Muslim polemics in South India: intimacies, mass publicity, and secularism - Menon, Nandagopal R. (Oxford University Press, 2024)
This book examines what unifies and separates various Sunni Muslim sects and incites polemics. It explores Islam as a body of information and cultural practices that focus on family and other social groups. The work also reveals the shared experience of being a persecuted religious minority in a Hindu majoritarian democracy